False memory in between-language conditions: a brief review on the effect of encoding and retrieving in different languages - Beato, Maria Soledad; Suarez, Mar; Cadavid, Sara; Albuquerque, Pedro B. (Frontiers in Psychology, 2023)
False memories have been extensively investigated over the past few decades using the Deese/Roediger-McDermott (DRM) paradigm. In this paradigm, participants study lists of words associatively related to a non-presented critical lure. During a memory test, these critical lures are falsely recalled or recognized. Most studies have focused on false memories that arise when both encoding and retrieval are conducted in the same language (i.e., within-language conditions), which is typically the participant's native or first language (L1). However, much less is known about false memories when critical lures appear in the memory test in a different language than the studied lists (i.e., between-language conditions), being one of them the participant's second language (L2). The main objective of this exhaustive review was to provide an overview of the current state of research on false recognition using the DRM paradigm in between-language conditions, where languages are switched between encoding and retrieval (i.e., L1L2 versus L2L1). The results revealed a language dominance effect in between-language false memories. In other words, false recognition rates were dependent on the study language, with a trend toward higher false recognition when words were enconded in the L1 (L1L2) compared to when words were encoded in the L2 (L2L1). This review enhances our understanding of how studying words in a first or second language affects false memory in the DRM paradigm, emphasizing the significance of investigating false memory in second language speakers and the necessity for further research in the field.